STRONGLY AND ALWAYS G#P-OPEN FUNCTIONS IN TOPOLOGY - Salih, Hula M (MAGISTRA, 2014)
In this paper, we first introduce a new class of open and closed functions called Generalized#p-open (G#p-open) ,Generalized#p- closed (G#p-closed) and we also introduce another new classs of open functions called strongly g#p-open and always g#p-open function which are stronger than g#p-open functions. Key words:g#p-open function , g#p-closed function,strongly g#p-open function ,always g#p-open function .